The osteoderms of baurusuchid crocodyliforms (Mesoeucrocodylia, Notosuchia) - Montefeltro, Felipe C. [UNESP] (Taylor & Francis, 2019)
Baurusuchidae is a clade of terrestrial crocodyliforms that thrived during the Late Cretaceous in South America. The members of this clade occupied top-predator roles in their habitats. Knowledge about the anatomy, the systematics, and the evolution of baurusuchids has increased profoundly in the past decade. Although aspects of their cranial and postcranial anatomy are becoming clearer, the configuration of the dermal armor remains neglected and little is known about the anatomy of these elements in the clade. The dermal skeleton of baurusuchids is described here in detail in terms of arrangement and morphology, the supposed absence of osteoderms in Pissarrachampsa sera is reevaluated, and a detailed comparison across Crocodyliformes is attempted. The description of the dermal armor, in particular that of the dorsum, revealed an unforeseen variation among baurusuchid taxa, including autapomorphic traits that were added to the diagnosis of taxa. The absence of osteoderms is confirmed for Pissarrachampsa sera based on new specimens, revealing this taxon as the only terrestrial crocodyliform known to lack dermal armor altogether. Comparisons with a diverse range of crocodyliforms revealed that the dorsal shield of baurusuchids is unique among crocodyliforms in terms of arrangement and morphology, and only a few notosuchians approach the condition seen in the clade. This study explores possible biomechanical implications of the unique dorsal shield of baurusuchids and provides information about possible phylogenetic signals, to be tested in future analyses of notosuchian systematics.